ByzRev 06.2024.078: Guglielmo Cavallo, Παραδείγματα. Le liste degli autori greci esemplari dall’antichità a Bisanzio: (Transmissions: Studies on Conditions, Processes and Dynamics of Textual Transmission 8). Berlin – Boston: De Gruyter 2024. - Xenophontos, Sophia (The Byzantine Review, 2024)
Guglielmo Cavallo, Παραδείγματα. Le liste degli autori greci esemplari dall’antichità a Bisanzio (Transmissions: Studies on Conditions, Processes and Dynamics of Textual Transmission 8). Berlin – Boston: De Gruyter 2024. 205 pp. – ISBN 978-3-11-102709-8